Behavior in Selecting Muslim Communities in the 2014 Legislative Election in Kapas District, Bojonegoro Regency - Safitri, Retno Ayu (UNUSA Press, 2019)
This research presents an analysis of the voting behaviour of Moslem people shown by residents of Kapas regency, Bojonegoro in 2014. This research is a descriptive analysis to explain the correlation between 4 variables in determining people’s vote in 2014’s legislative election in Kapas regency. These variables are: legislative party/nominees proposed programme, identification of the party, money politics, and afiliated religious organization. The researcher used quantitative method to collect the data and descriptive analysis in the forms of data distribution and data frequency which were collected using questionnaires. In addition to that, the researcher used Chi Square testing and contingency coefficient to find whether the variables are correlated to each other. There are three general approach to describe the voting behaviour in this research: sociology approach, psychology approach, and rational approach. The majority of theories referred by the researcher were theories by Paul F. Lazarfeld- Bernard Berelson, Angus Campbel, and Anthony Downs. The outcome of this research suggests that two of the aforementioned variables have significant influence in determining voting behaviour: legislative party/nominee proposed programme and money politics. The two other variables which are political party identification and afiliated religious organization are not influential in determining voting behaviour of Kapas’ residents in 2014’s legislative election.